Estabelecimento de carioplastos e citoplastos de catetos, pecari tajacu (linnaeus, 1758), visando a clonagem por transferência nuclear de célula somática em taiassuídeos - Borges, Alana Azevedo (Universidade Federal Rural do Semi-Árido, 2020)
The direction of the first steps for the achievement of somatic cell nuclear transfer (SCNT) in collared peccary will guarantee an effective tool in the conservation of the species, in view of its accelerated population decrease and its essential ecological activity for the ecosystem. Therefore, the present thesis was divided into two steps (three experiments per step), being the first step the study of the donor cells of nucleus or karyoplast and the second stage, the study of the donor cells of cytoplasm or cytoplasts. Thus, in view of the importance of acknowledge quality karyoplast for SCNT, we initially established five cell lines of collared peccary fibroblasts, monitoring viability, metabolic activity and oxidative stress, according to the effects of the number of passages (first, third and tenth) and cryopreservation. Although there is no effect of these criteria on viability, cells in tenth passage had a reduction in their metabolism. Additionally, frozen/thawed cells had an increase in the number of reactive oxygen species and mitochondrial membrane potential. Moreover, knowing the importance of maintaining these cells stored in a biobank properly, we optimize the cryoprotectant solution used in the slow freezing of collared peccary fibroblasts. Thus, the solution composed of 10% dimethyl sulfoxide (DMSO) with 0.2 M sucrose and 50% fetal bovine serum (FBS) was considered the most efficient solution in maintaining the viability, proliferative activity, metabolism and adequate levels of oxidative stress of somatic cell cells, when compared to solutions in the absence of sucrose and with 10% FBS in different combinations. Finally, an essential step in establishing the karyoplast for SCNT is the synchronization of cells in G0/G1 of the cell cycle. Thus, we evaluated different cell cycle synchronization methods: (i) serum suppression (SS) for one to four days, (ii) contact inhibition (CI) for one to three days and (iii) chemical agents [DMSO, 6-dimethylaminopurine (6-DMAP), cyclohexamide (CHX), and cytochalasin B (CB)] for one to two days, in terms of their effects on G0/G1 synchronization and viability. Thus, we observed that the IC for three days was the most efficient method for synchronizing the cell cycle and maintaining the viability of collared peccary fibroblasts. Consequently, with these three experiments, we have established karyoplast stage of SCNT in collared peccary, obtaining quality cells and able to be used as nuclear donors. In the second stage, we initially adjusted the in vitro maturation (IVM) conditions of collared peccary oocytes, evaluating the IVM time and the effect of the epidermal growth factor (EGF) on the meiotic ability. Thus, we concluded that 48 h is the appropriate period for oocyte IVM when compared to 24 h, according to meiotic potential. Still, it was observed that EGF can be used to optimize the IVM medium. Finally, in the third experiment, we evaluated the developmental ability of these oocytes after artificial activation, using ionomycin as the primary activator and comparing different secondary activators (6-DMAP, CHX and CB). We found that chemical activation using ionomycin and 6-DMAP was the most efficient combination, with this thesis achieving as a significant result, a rate of 27.6% of blastocysts of collared peccaries derived from oocyte artificial activation. In summary, we got karyoplast and cytoplasts that may be employed in the SCNT of collared peccary, leaving the point the fundamental steps for the cloning of this species. Furthermore, it is emphasized that the knowledge generated here can be applied for in vitro fertilization, studies understanding of embryonic development, production cells induced to pluripotency, and toxicity assessments. Therefore, this work was a great step for the conservation of collared peccaries
Keywords: Vida selvagem; Clonagem; Biobancos; Ciclo celular; Ativação oocitária; Produção de embriões; Wild life; Cloning; Biobanks; Cell cycle; Oocyte activation; Embryo production; CIENCIAS AGRARIAS::MEDICINA VETERINARIA